FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI INDUSTRI KECIL DI KABUPATEN KERINCI - Ismanto, Hadi; Syofyan, Efrizal; Yulhendri, Yulhendri (Program Studi Magister Ilmu Ekonomi, 2014)
This study aims to analyze and determine the effect of: (1) working capitalto small industrial production in the Kerinci regency, (2) the raw material for theproduction of small industries in Kerinci regency (3) labor to the production ofsmall industries in the district of Kerinci (4) goverment policy to small industrialproduction in the Kerinci regency (5) working capital, raw materials, labortogether and goverment policy to yield a small industrial production in theKerinci regency. research data in the form of panel data from 2006 - 2010 with 12districts in Kerinci (n = 60). This research uses the methods of analysis toolsOrdinary Least Squared (OLS). The dependent variable in the study was smallindustrial production. While the independent variable in this study is workingcapital, raw materials labor and goverment policy. The research concludes thatthe working capital significantly influence the results of a small industrialproduction in the Kerinci regency. Then, the value of raw materials alsosignificantly influence the results of a small industrial production in the Kerinciregency. In addition, labor does not significantly influence the results of a smallindustrial production in the Kerinci regency. So, goverment policy alsosignificantly influence the results of a small industrial production in the Kerinciregency. Based on these results the policies can be suggested that employers mustincrease their working capital in order to smooth the production process so thatthe yield can always be improved. Particularly through local government to localgovernment Kerinci can simplify and guarantee the existence of raw materialssmall industries that exist in the Kerinci regency. In addition, small industrialentrepreneurs are expected to also have alternative raw materials to maintain theavailability of basic raw materials.Keywords: Small Industrial Production, Working Capital, Raw Materials andLabor